2016
DOI: 10.1038/nchem.2691
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between defects, disorder and flexibility in metal-organic frameworks

Abstract: Metal-organic frameworks are a novel family of chemically diverse materials, which are of interest across engineering, physics, chemistry, biology and medicine-based disciplines. Since the development of the field in its current form more than two decades ago, priority has been placed on the synthesis of new structures. However, more recently, a clear trend has emerged in shifting the emphasis from material design to exploring the chemical and physical properties of structures already known. In particular, alt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
331
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(343 citation statements)
references
References 55 publications
8
331
0
4
Order By: Relevance
“…Utilising modulators in MOF syntheses can result in the creation of defects, in the form of missing linkers and/or clusters with concomitant incorporation of capping modulators, which can impart the MOF with interesting and unusual physical properties. 31,32 Recent studies have shown that modulator incorporation and subsequently defectivity can be correlated to the pK a of the modulating agent.…”
Section: -16mentioning
confidence: 99%
“…Utilising modulators in MOF syntheses can result in the creation of defects, in the form of missing linkers and/or clusters with concomitant incorporation of capping modulators, which can impart the MOF with interesting and unusual physical properties. 31,32 Recent studies have shown that modulator incorporation and subsequently defectivity can be correlated to the pK a of the modulating agent.…”
Section: -16mentioning
confidence: 99%
“…[176] Studies of the mechanical properties and energy absorption in single crystals of four isostructural samples belonging to the UiO type of MOF highlighted plasticity and endothermicity during deformation. [179] At stresses higher than 2 GPa, energy absorption reaches 3-4 kJ per gram (for reference, about 4 kJ of energy per gram is released on the explosion of TNT, trinitrotoluol equivalent).…”
Section: Mechanical Metamaterialsmentioning
confidence: 99%
“…Porous crystalline solids are an important class of heterogeneous catalysts with, for example, zeolites as one of the most prominent examples ,. Metal‐Organic Frameworks (MOFs) are an emerging class of crystalline porous solids that recently have received a lot of attention . There are a several major reasons that MOFs are popular in (catalysis) research.…”
Section: Introductionmentioning
confidence: 99%